The Relationship between Free Time Satisfaction and Stress Levels of Elite-Level Student-Wrestlers - Fatih Yasarturk; Hayri Akyüz; Ismail Karatas; Mutlu Turkmen (MDPI AG, 2018)
The purpose of this research was to examine the relationship between free time satisfaction and stress levels of elite level student wrestlers according to some demographic factors. The sample of the study consisted of 119 (85 male and 34 female) elite level student wrestlers who participated in the Wrestling National Team camp in 2018. As data collection tools, “Personal Information Form”, “Stress Scale in Working Life: SSWL”, and “Free Time Satisfaction Scale: FTSS” were used. In the analysis of the derived data, t-test, Mann-Whitney U, and Kruskal-Wallis were used, and Pearson Correlation test was applied to examine relations between study variables. There was no significant difference in the t-test results according to the “gender” variable (p > 0.05). There was a meaningful, low-level negative correlation between the “age” variable and social, aesthetic, sub-dimensions of stress scale. As a result, this study found that participants’ free time satisfaction levels were related to age; and stress levels were related to age, sport year, national team year, and income level.